Experimental models of leprosy - A. A. Kubanov; A. E. Karamova; A. A. Vorontsova; P. A. Kalinina (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Leprosy (Hansen's disease) is a chronic granulomatous bacterial disease which mainly affects skin and peripheral nervous system. Leprosy is caused by the obligate intercellular pathogen known as Mycobacterium leprae. Creating experimental models of leprosy is associated with serious problems due to biological characteristics of the pathogen. Numerous attempts to develop experimental models on different types of animals resulted in a few reproducible models on mice and nine-banded armadillos. Strains of knockout mice with genetic defects caused by site-directed mutagenesis are used as a basis for different leprosy models. Experimental models of leprosy are used for screening of anti-leprosy drugs, detection of drug resistance, studies on the pathogenesis of leprosy, production and evaluation of viability of M. leprae, developing of anti-leprosy vaccines.